The Effect of MAPP Compatibilizing Agent on the Mechanical and Thermal Properties of Polypropylene/PLA Blends - Z. Engku Zawawi, E.; Z. Romli, A.; F. Mat Suli, S.; Amirrudin Isnin, M. (International Journal of Engineering and Technology, 2019)
In this study, the polymer blends were prepared in the ratios of Polypropylene (PP) to Polylactic acid (PLA) of 70:30 by weight. Maleic anhydride-grafted polypropylene (MAPP) was used as a coupling agent to improve the compatibility between PP and PLA. The MAPP was added into the blend in the ratio of 0, 3, 6 and 9% wt. The polymer blends were prepared by extrusion process using twin screw extruder. The effects of MAPP content on the mechanical and thermal properties of PP/PLA blend were investigated. The result of tensile strength shows no significant increased with the addition of MAPP content. However, Young modulus and Izod impact strength shows significantly increased with the addition of MAPP content. Tensile modulus increased up to 43% with the addition of 6% wt. MAPP. TGA results show that blending PP with PLA cause increased the thermal stability of PLA. The incorporation of 6 % MAPP has shifted the initial weight loss of PP component towards lower temperature.Â Â